Transcatheter and surgical aortic valve replacement in patients with bicuspid aortic valve - Husso A; Airaksinen J; Juvonen T; Laine M; Dahlbacka S; Virtanen M; Niemelä M; Mäkikallio T; Savontaus M; Eskola M; Raivio P; Valtola A; et al. (Germany, 2022)
Objectives: To compare the outcomes after surgical (SAVR) and transcatheter aortic valve replacement (TAVR) for severe stenosis of bicuspid aortic valve (BAV).
Methods: We evaluated the early and mid-term outcome of patients with stenotic BAV who underwent SAVR or TAVR for aortic stenosis from the nationwide FinnValve registry.
Results: The FinnValve registry included 6463 AS patients and 1023 (15.8%) of them had BAV. SAVR was performed in 920 patients and TAVR in 103 patients with BAV. In the overall series, device success after TAVR was comparable to SAVR (94.2% vs. 97.1%, p = 0.115). TAVR was associated with increased rate of mild-to-severe paravalvular regurgitation (PVR) (19.4% vs. 7.9%, p < 0.0001) and of moderate-to-severe PVR (2.9% vs. 0.7%, p = 0.053). When newer-generation TAVR devices were evaluated, mild-to-severe PVR (11.9% vs. 7.9%, p = 0.223) and moderate-to-severe PVR (0% vs. 0.7%, p = 1.000) were comparable to SAVR. Type 1 N-L and type 2 L-R/R-N were the BAV morphologies with higher incidence of mild-to-severe PVR (37.5% and 100%, adjusted for new-generation prostheses p = 0.025) compared to other types of BAVs. Among 75 propensity score-matched cohorts, 30-day mortality was 1.3% after TAVR and 5.3% after SAVR (p = 0.375), and 2-year mortality was 9.7% after TAVR and 18.7% after SAVR (p = 0.268) CONCLUSIONS: In patients with stenotic BAV, TAVR seems to achieve early and mid-term results comparable to SAVR. Type 1 N-L and type 2 L-R/R-N BAV morphologies had higher incidence of PVR. Larger studies evaluating different phenotypes of BAV are needed to confirm these findings.